2020
DOI: 10.7150/ijms.49849
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of mitochondrial uncoupling protein 2 exacerbates mitophagy and cell apoptosis after cerebral ischemia and reperfusion injury in mice

Abstract: Objective: Uncoupling protein 2 (UCP2) is a member of inner mitochondrial membrane proteins and deletion of UCP2 exacerbates brain damage after cerebral ischemia/reperfusion (I/R). Nevertheless, its functional role during cerebral I/R is not entirely understood. The objective of present study was to explore the influence of UCP2 deletion on mitochondrial autophagy (mitophagy) and mitochondria-mediated cell death pathway after cerebral I/R. Methods: UCP2-/-and wildtype (WT) mice were subjected to 60 min middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Studies have confirmed that the upregulation of UCP2 can reduce ROS production in cerebral I/R damage [33]. Our previous study showed that UCP2 deficiency increased ROS production after cerebral I/R damage [34]. Taken together, the present study suggests that UCP2 deficiency enhances NLRP3 inflammasome activation by increasing ROS production in the context of hyperglycemia-exacerbated I/R damage.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have confirmed that the upregulation of UCP2 can reduce ROS production in cerebral I/R damage [33]. Our previous study showed that UCP2 deficiency increased ROS production after cerebral I/R damage [34]. Taken together, the present study suggests that UCP2 deficiency enhances NLRP3 inflammasome activation by increasing ROS production in the context of hyperglycemia-exacerbated I/R damage.…”
Section: Discussionsupporting
confidence: 84%
“…From this perspective, it would be important to broad our knowledge by investigating the fine mechanisms of action of UCP2. In this regard, a link between UCP2 protection and autophagy stimulation has recently emerged with particular regard to cardiomyopathies, including ischemia/reperfusion (I/R) injury and cardiac hypertrophy, acute kidney injury and cerebral ischemia [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of mild mitochondrial uncoupling secondary to changes in Cx43 hemichannels may have consequences on reactive oxygen species (ROS) generation ( Cadenas, 2018 ) and mitophagy ( He et al, 2020 ). Indeed, isolated cardiomyocytes from Cx43-deficient mice become resistant to protection by the ATP-dependent potassium channel opener diazoxide due to impaired mitochondrial ROS production ( Heinzel et al, 2005 ), whereas induction of Cx43 hemichannel permeability by nitric oxide donors increases ROS production in cardiac SSM ( Soetkamp et al, 2014 ).…”
Section: Function Of Mitochondrial Connexins Under Physiological Cond...mentioning
confidence: 99%